Blockchain for smart city - public service integration by strategic alliance. (5th October 2020) - Zhang, Yi; Xie, Chenlei; Ma, Xiaoli
The smart city, as a developing strategy for global economy, has been initiated in many countries and has exhibited a booming future. There are various studies suggesting that the blockchain is an indispensable tool for smart city construction. However, adapting it to smart city strategy is still an open challenge. The objectives of this paper are to apply blockchain to smart city's strategic decision making in the form of strategic alliance (SA) and provide suggestions for smart city development. The solution proposed in this research is to design an SA, with a focus on promoting the organisational structure of the information transmission alliance using the blockchain and to organise the smart services by promoting the integration of smart solutions and the knowledge of blockchain. This research surveys literature data, and classifies and analyses the collected literature data. According to the study, we develop a smart city model that applies the blockchain technology.